Moderasi Beragama dalam Bingkai antar Umat Beragama - Kurniawati, Wakhidah; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
The Indonesian is multicultural country. It’s diversity includes differences in culture, religion, race, language, ethnicity, tradition and others. In a such multicultural society, there are frequent tensions and conflicts among cultural groups and have impacts on harmony in life. The purpose of this paper is to discuss the diversity of Indonesian culture, its religious moderation in the diversity and role of religious educators in realizing Indonesian national peace. The method used is a library research. The conclusion of this study is that multicultural life requires multicultural understanding and awareness that respects diversity, and willingness to interact with anyone fairly. A religious attitude of moderation is needed in the form of recognition of the existence of other parties, being tolerant, respecting differences of opinion and not forcing the will through violence. The role of the government, community leaders, and religious guidance is needed to socialize, develop religious moderation to the community for the sake of the realization of harmony and peace.